Ordovician carbonate-shale system of the part of the Canning Basin, W.A. - Teoh, Ying Jia (Curtin University, 2013)
The Canning Basin is a large but relatively poorly explored Paleozoic basin in remote Western Australia. In a study of Middle Ordovician carbonate systems in 38 petroleum wells, facies associations for the Nita and Goldwyer Formations were evaluated to determine depositional environments. Integrated prediction error filter analysis (INPEFA) curves were used for subsurface correlation, sequence stratigraphy and shale gas assessment, and findings were correlated with global sea-level cyclicity.